Farmers’ Preferences for Mobile Agro Advisory Services - Duraisamy Prabha; R Arunachalam (Journal of Extension Education, 2017)
This study was conducted in Coimbatore district of Tamil Nadu to understand the service preferences of the mobile agro advisory services offered by the public extension system. The agro advisories offered by the e-extension centre of Tamil Nadu Agricultural University were selected for the study. A sample of 200 respondents was selected employing proportionate random sampling method. The study was carried out in terms of dimensions viz., technical components, message frequency and timings, message physical dimension, message channel and message follow up. Results of the survey showed that among the technical components majority of the respondents opined that the information on advance warning of weather risks was very much adequate, the messages on plant protection were relevant and that the messages on advance warning of weather risks were timely. With reference to the message frequency, a majority preferred frequency of the messages on daily basis and preferred to receive messages during mornings.